Comparison of 3‐D mandibular surfaces generated by MRI and CT. (15th October 2021) - Maeda, Jun; Tanikawa, Chihiro; Nagata, Namiki; Lim, Jaeyeon; Kreiborg, Sven; Murakami, Shumei; Yamashiro, Takashi
Abstract: Objective: The purpose of this study was to evaluate the errors of three‐dimensional mandibular surfaces generated using magnetic resonance imaging (MRI) when computed tomography (CT) was set as the gold standard. Settings and sample population: Seven patients with orthognathic deformities who had undergone CT and MRI scans were included in the study. Materials and Methods: Mandibular surfaces were generated on each CT and MR image by the surface‐rendering method. Intra‐individual reliability between CT and MRI was statistically tested by the confidence limits of agreement (LOA) for systematic error, 95% confidence interval minimal detectable change (MDC95 ) for random error and intra‐class correlation coefficient (ICC). Results: The average total error was 1.6 mm. The greatest MDC95 was observed in the coronoid region in all directions. The other regions showed MDC95 values of < 1.8 mm (transvers direction), 3.5 mm (vertical direction) and 1.7 mm (antero‐posterior direction). ICCs showed 'almost perfect' agreement with respect to all regions. Conclusion: Random errors were quantified for 3‐D rendering of the mandible from MRI data. Although the coronoid region showed the greatest errors, the other regions of the mandibular surfaces generated using MRI were able to be evaluated.